Study on Epidemiology of Hypertension in a Tertiary Care Hospital - Aasif, Mohd. (International Journal of Pharmaceutical & Biological Archive, 2021)
An epidemiological study of hypertension (HTN) was carried out in a tertiary care hospital located in Dehradun, Uttarakhand, India. Several parameters such as gender, age, education, economic status, comorbid state, smoking habit of person, body mass index (BMI), physical activity, family history of HTN, salt intake, habit of drinking alcohol, physical activity of patients, waist-hip ratio, and medication usage in HTN were considered to assess the epidemiology of HTN. Results revealed that the prevalence of HTN was more in male than female patients with highest incidence in the age group of 40–60 years of age. Certain health risk factors such as urban areas, lower educational qualification, and higher BMI also affected significantly HTN. In addition, smoking habits, drinking habits, physical activity, comorbid state, and waist-hip ratio also influenced greatly the HTN in the studied population.